Regency Erosion Prediction Analysis and Erosion Hazard in the Malino Sub-DAS Jenebarang Watershed, Gowa District - Saida Saida; Annas Boceng; Maimunah Nontji; Bakhtiar Ibrahim; Mudttasad Mudttasad (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study aimed to analyze erosion prediction and erosion hazard levels in the Malino Sub-Watershed, Jeneberang Watershed, Gowa Regency, South Sulawesi Province. The research was conducted from August to September 2024 in the Malino Sub-Watershed, located in Tinggimoncong District. The study employed the Universal Soil Loss Equation (USLE) method to estimate soil erosion rates based on rainfall erosivity, soil erodibility, slope length and steepness, land cover, and conservation practices. The results showed that secondary dryland forest and paddy field land uses had very low erosion rates, with values of 11.86 tons/ha/year and 5.92 tons/ha/year, respectively. Moderate erosion levels were found in plantation forest, dryland farming, and mixed dryland agriculture, with erosion rates ranging from 23.52 to 87.68 tons/ha/year. The highest erosion rate occurred on scrubland, reaching 805.59 tons/ha/year, which was classified as a very severe erosion hazard level. The findings indicate that land cover conditions, slope characteristics, and conservation practices strongly influence erosion intensity in the Malino Sub-Watershed.